2015
DOI: 10.1021/ml500478m
|View full text |Cite
|
Sign up to set email alerts
|

PNA-Based Multivalent Scaffolds Activate the Dopamine D2 Receptor

Abstract: Peptide nucleic acid scaffolds represent a promising tool to interrogate the multivalent effects of ligand binding to a membrane receptor. Dopamine D2 receptors (D2R) are a class of G-protein coupled receptors (GPCRs), and the formation of higher-ordered structures of these receptors has been associated with the progression of several neurological diseases. In this Letter, we describe the synthesis of a library of ligand-modified PNAs bearing a known D2R agonist, (±)-PPHT. The D2R activity for each construct w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…However, many challenges remain, and various aspects of this field still require exploration. First, numerous biological molecules capable of bivalent or multivalent interactions have not yet been explored in regard to their use in the design of biosensors [130][131][132][133][134][135]. Second, precisely designed nanostructures are required for biosensors, particularly those used for detecting viruses; this is because they express unique patterns of antigen arrays.…”
Section: Discussionmentioning
confidence: 99%
“…However, many challenges remain, and various aspects of this field still require exploration. First, numerous biological molecules capable of bivalent or multivalent interactions have not yet been explored in regard to their use in the design of biosensors [130][131][132][133][134][135]. Second, precisely designed nanostructures are required for biosensors, particularly those used for detecting viruses; this is because they express unique patterns of antigen arrays.…”
Section: Discussionmentioning
confidence: 99%
“…The geometry and distance between the ligands can be adjusted based on the hybridization instructions, providing a rapid assessment of the optimal solution for tight binding and efficacy (Figure 3a). [83][84][85][86][87][88] Moreover, assemblies of PNA-ligand conjugates have been found to be functional in vivo (Figure 3b). 89 Specifically, a PNA-ligand conjugate that targets the α v β 3 integrin, a trimeric receptor overexpressed in many cancers, showed 100-fold enhanced binding when oligomerized, resulting in 50% reduction of tumor colonies in a mouse model.…”
Section: Supramolecular Drugsmentioning
confidence: 99%
“…Previously, we have shown that L Kγ-PNA (Figure 1b) is a versatile scaffold to attach a range of functional groups and small molecules without compromising the ability of PNAs to bind to a complementary nucleic acid sequence. 3841 Previous work has demonstrated the advantageous properties of using a PNA to target proteins via multvalent display. 38, 39, 4247 …”
mentioning
confidence: 99%
“…3841 Previous work has demonstrated the advantageous properties of using a PNA to target proteins via multvalent display. 38, 39, 4247 …”
mentioning
confidence: 99%